Development of gypsum plasterboard embodied with microencapsulated phase change material for energy efficient buildings - Maitiniyazi Bake (KeAi Communications Co., Ltd., 2021)
Phase change materials (PCMs) have been used in the development of building materials with higher thermal energy storage capacity. Especially, PCM incorporated gypsum plasterboard has been described to decrease the cooling demand of building by up to 35%. However, it’s significantly important to fabricate and characterise the thermal/physical properties of PCM-gypsum plasterboard accurately. This paper presented the fabrication process and property measurement of gypsum plasterboard integrated with microencapsulated PCM (mPCM). Property measurement included scanning electron microscope (SEM) technique, sting, density measurement, compressive strength test, and thermal conductivity testing. The characterisation results show that: (i) the gypsum plasterboard enhanced with 5% and 15% PCM claim 5.36 and 4.34 MPa respectively; (ii) with the addition of 15% PCM, the gypsum plasterboard presented the lowest value of thermal conductivity as 0.139 W/mK; (iii) The mPCM-gypsum plasterboard also operates longer period of time than gypsum plasterboard with higher temperature of roughly 1.5 °C especially during discharging period; (iv) The mPCM-pasteboard provided 0.4 W/min higher stored energy than gypsum plasterboard due to the addition of mPCM.